Ngai Tahu seafood: A case study in business development - Chris Nixon (New Zealand Institute of Economic Research (NZIER), 2003)
This paper examines the business development process undertaken by Ngai Tahu Seafood. An investigation of the business development process involves an examination of the opportunities and constraints that Ngai Tahu Seafood has faced in building up, capitalising on, and expanding their seafood business interests. The aim is to develop a framework that gives a consistent assessment of the Ngai Tahu's seafood business so that we can illustrate how aboriginal peoples can effectively create sustainable long-term businesses. Of particular interest, is the ability of Ngai Tahu Seafood to create scale economies from an industry that traditionally was dominated by small-scale operators.
Keywords: 330; Meeresprodukt; Neuseeland